Muscle co-contraction and pre-activation in knee and ankle joint during a typical Tai Chi brush-knee twist-step - Yu, H.; Wang, J.; Mao, M.; Song, Q.; Zhang, C.; Fong, D. T. P.; Sun, W. (Research in Sports Medicine, 2023)
This study aimed to investigate the co-contraction and pre-activation of agonistic and antagonistic muscles in experienced Tai Chi (TC) practitioners during normal walking (NW) and brush-knee twist-step (BKTS). The electromyographic activities of rectus femoris, biceps femoris, and tibialis anterior and lateral gastrocnemius muscles were collected during BKTS and NW in 28 TC practitioners. The pre-activation of knee and ankle joints before initial landing of left foot, and the co-contraction of knee and ankle joint in double-stance phase I (DSI), single-stance phase (SS), double-stance phase II (DSII), and swing phase (SW) were calculated during BKTS and NW. Ankle co-contraction significantly increased during DSI and SS in BKTS movements than compared with that in NW. For DSI and SW, SS and DSII, and DSII and SW, a significant difference was found in BKTS. The pre-activation of knee joint significantly decreased in BKTS and NW. This study indicated greater ankle joint muscle co-contraction in DSI and SS of stance phase and lower knee joint muscle co-contraction and pre-activation than in NW in BKTS movement. In addition, greater ankle joint muscle co-contraction was observed in the DSI, SS, and DSII of stance phase than those of swing phase in BKTS movement.